The Stratigraphy and Lithology of the Glaciogenic Sediments of the Two Harbors Area, Northeastern Minnesota - Gross, Laura Blanche (1982)
A Thesis submitted to the faculty of the Graduate School of the University of Minnesota by Laura Blanche Gross in partial fulfillment of the requirements for the degree of Master of Science, December 1982. Plates I-II referenced in the thesis are also attached to this record, along with the Legend that explains both plates. Five texturally distinct sedimentary units are differentiated in the Quaternary deposits of the Two Harbors and Whyte quadrangles in Lake County, northeastern Minnesota. Their specific properties are attributed to differing (1) bedrock sources, (2) conditions of glacier flow, and (3) methods and environments of deposition. These glacially derived sediments, including a clay-rich diamicton, record the advance, stagnation, and retreat of the Rainy and Superior Lobes, two appendages of the Laurentide Ice Sheet, sometime after 30,000 years B.P. The dominant surficial deposit of the northwestern half of the Whyte quadrangle is a gray to brown, sandy to stony till, the Sullivan Lake Formation. The average sand:silt:clay ratio is 76:21:03. The clasts and surface boulders are predominantly granophyre, granite, greenstone, basalt, and gabbro-diabase. The source of sediment for this formation is the underlying Duluth Complex and other Precambrian igneous and metamorphic sources cropping out to the north and northeast. The Sullivan Lake Formation was deposited by an actively moving, wet-based glacier. For the most part, it was deposited in the basal zone as a lodgement till. This till is attributed to the Rainy Lobe advance from the northeast about 20,500 Â± 400 years B.P. (Wright, et al., 1973). Geomorphic features attributed to this ice advance are the northeast- southwest trending Toimi drumlins, small eskers, and a tunnel valley, partially occupied by Sullivan Lake. The glaciogenic sediments that comprise the southeastern half of the Whyte quadrangle and the northern part of the Two Harbors quadrangle (the Cromwell Formation) are markedly different from the Sullivan Lake Formation. They are a ...